Ultrasound-Guided Synovial Biopsies of Wrists, Metacarpophalangeal, Metatarsophalangeal, Interphalangeal Joints, and Tendon Sheaths - Lazarou, Ilias; Kelly, Stephen Gerard; Meric de Bellefon, Laurent (Frontiers in Medicine, 2019)
Ultrasound-guided synovial biopsy (UGSB) is a minimally-invasive procedure which allows quality synovial tissue retrieval. In this article, we will discuss overarching principles of the procedure performed in wrists, metacarpophalangeal (MCP), metatarsophalangeal (MTP), interphalangeal joints (IP), and tendon sheaths, including basic sonoanatomy, entry site and biopsy technique, as well as special considerations for each structure whenever relevant.